Three challenges that the COVID-19 pandemic represents for psychiatry - Kesner, Ladislav; Horáček, Jiří (British journal of psychiatry, 2020)
The evolving COVID-19 pandemic and its likely consequences add to the already substantial psychosocial burden caused by global problems, existential threats and heightened uncertainty, which are increasingly confronting communities worldwide. Here we briefly outline three challenges for clinical psychiatry and research, related to coping with the social epidemiology of negative moods, stress and socially mediated traumatic experiences brought on by these adverse developments.
Keywords: Pneumonia, Viral; pandemie; Adaptation, Psychological; Humans; koronavirové infekce; duševní zdraví; sociální média; Pandemics; Coronavirus Infections; Psychology; lidé; Irritable Mood; podrážděnost; nejistota; Stress, Psychological; Social Media; Uncertainty; adaptace psychologická; psychický stres; Global Health; celosvětové zdraví; psychologie; virová pneumonie; Mental Health